Evaluasi Kinerja Saluran Sekunder Irigasi (Studi Kasus Daerah Irigasi Kampili Kecamatan Pallangga Kabupaten Gowa) - Trimalino, Tedy; Virlayani, Asnita; Gaffar, Farida (Fakultas Teknik Universitas Muhammadiyah Parepare, 2024)
The Kampili irrigation system has experienced some damage, such as damage on channel body by ages, wild plants due to lack of maintenance and there are several channels that are not used to irrigate land according to the planned drainage area. The purpose of this study was to analyze secondary channel water loss and analyze the efficiency value of water distribution. This research was held on September 2024 and analyzed using the experimental methods. The results showed that the level of efficiency of the secondary channel was 79% which was still in the good category. That means it still functions well to channel water to the tertiary channels in Pallangga Village. This level of efficiency is supported by the physical structure of irrigation which also still in a good condition. In addition to water loss due to seepage, water loss was also caused by evaporation of 0.004209 m3/s but the level of efficiency still in standard.